2010
DOI: 10.1016/j.jplph.2009.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response of pepper plants to wilt induced by Verticillium dahliae and soil water deficit

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…In fact, the photochemical efficiency of PSII measured after the darkening period (Fv/Fm) remained almost constantly close to 0.8, the maximum value recorded under optimal environmental conditions for most plant species [44][45][46]. Signs of photoinhibition can be observed when Fv/Fm declines and thus a decrease of the photochemical efficiency of PSII, called the 'down-regulation of photochemistry', occurs, revealing permanent photoinhibition [47][48][49]. Furthermore, the increase in NPQ provides protection against damage by excessive energy, in agreement with previous studies on grapes [40], pepper [50] and Amur grapes (Vitis Amurensis Rupr.)…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the photochemical efficiency of PSII measured after the darkening period (Fv/Fm) remained almost constantly close to 0.8, the maximum value recorded under optimal environmental conditions for most plant species [44][45][46]. Signs of photoinhibition can be observed when Fv/Fm declines and thus a decrease of the photochemical efficiency of PSII, called the 'down-regulation of photochemistry', occurs, revealing permanent photoinhibition [47][48][49]. Furthermore, the increase in NPQ provides protection against damage by excessive energy, in agreement with previous studies on grapes [40], pepper [50] and Amur grapes (Vitis Amurensis Rupr.)…”
Section: Discussionmentioning
confidence: 96%
“…This might represent a common leaf adaption to hypoxia stress based on similar reports in oak (Pezeshki ) and citrus (Arbona et al ). The reduction in net photosynthesis has previously been attributed to stomatal closure, which reduces the CO 2 concentration within leaves (Gravatt and Kirby , Pascual et al ). However, other researchers have suggested that changes in hormone levels produced or elicited by hypoxia may induce stomatal closure and/or damage to the leaf photosynthetic apparatus (Bradford and Hsiao , Else et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Menconi et al (1995) have suggested that plant water relations play a key role in the activation and modulation of an antioxidant defense mechanism under drought conditions. Leaf RWC serves as a reference parameter to reflect the intensity of moisture stress that is caused by a soil water deficit (Pascual et al 2010;Sánchez-Rodríguez et al 2010). In wheat, Rampino et al (2006) have identified those genotypes that are tolerant or sensitive to water stress, based on RWC values.…”
Section: Discussionmentioning
confidence: 99%